Protein Disulfide Isomerases Regulate IgE-Mediated Mast Cell Responses and Their Inhibition Confers Protective Effects During Food Allergy - Krajewski, Dylan; Polukort, Stephanie H.; Gelzinis, Justine; Rovatti, Jeffrey; Kaczenski, Edwin; Galinski, Christine; Pantos, Megan; Shah, Nickul N.; Schneider, Sallie S.; Kennedy, Daniel R.; Mathias, Clinton B. (Frontiers in Immunology, 2020)
The thiol isomerase, protein disulfide isomerase (PDI), plays important intracellular roles during protein folding, maintaining cellular function and viability. Recent studies suggest novel roles for extracellular cell surface PDI in enhancing cellular activation and promoting their function. Moreover, a number of food-derived substances have been shown to regulate cellular PDI activity and alter disease progression. We hypothesized that PDI may have similar roles during mast cell-mediated allergic responses and examined its effects on IgE-induced mast cell activity during cell culture and food allergy. Mast cells were activated via IgE and antigen and the effects of PDI inhibition on mast cell activation were assessed. The effects of PDI blockade in vivo were examined by treating mice with the irreversible PDI inhibitor, PACMA-31, in an ovalbumin-induced model of food allergy. The role of dietary PDI modulators was investigated using various dietary compounds including curcumin and quercetin-3-rutinoside (rutin). PDI expression was observed on resting mast cell surfaces, intracellularly, and in the intestines of allergic mice. Furthermore, enhanced secretion of extracellular PDI was observed on mast cell membranes during IgE and antigen activation. Insulin turbidimetric assays demonstrated that curcumin is a potent PDI inhibitor and pre-treatment of mast cells with curcumin or established PDI inhibitors such as bacitracin, rutin or PACMA-31, resulted in the suppression of IgE-mediated activation and the secretion of various cytokines. This was accompanied by decreased mast cell proliferation, FcRI expression, and mast cell degranulation. Similarly, treatment of allergic BALB/c mice with PACMA-31 attenuated the development of food allergy resulting in decreased allergic diarrhea, mast cell activation, and fewer intestinal mast cells. The production of TH2-specific cytokines was also suppressed. Our observations suggest that PDI catalytic activity is essential in the regulation of mast cell activation, and that its blockade may benefit patients with allergic inflammation.